Effect of process parameters on yield and conversion of jatropha biodiesel in a batch reactor - Kabbashi, Nassereldeen Ahmed; Nurudeen, Ishola; Alam, Md Zahangir; Mirghani, Mohamed Elwathig Saeed (OMICS Group - Open Access Publisher, 2015)
In a quest for environmental friendly energy source with least pollutants emission due to issues of global warming coupled with dwindling reserve of the fossil fuel, researchers have intensified study on renewable fuels. Among these renewable energy sources, biodiesel stands prominent. Biodiesel production is largely by transesterification of transglycerides of fatty acids almost always in a batch reactor. Of importance in the yield generation and fatty acid methyl esters conversion is the feedstock purity, control of reagents use in production and operation parameters alteration. This is geared towards achieving optimum resource conservation while also minimizing cost and materials wastage. In this study biodiesel was produced from hydrolysate (free fatty acids from hydrolyzed Jatropha curcas oil) using calcinated niobic acid catalyst at controlled rates of process parameters. Yield and conversion up to 97.7% and 100% respectively of the alkyl esters produced. This informs the influence of process parameters significantly on the throughput of the final product.